Hydrogen Bonds - Jabłoński, Mirosław (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint is excellent proof that, despite more than a hundred years of research into hydrogen bonds, they are still an interesting and fundamental topic in the natural sciences. The collected articles deal with various aspects of the existence of hydrogen bonds and show human ingenuity in the field of inventing and applying various techniques, both experimental and theoretical, in order to describe them more fully.